Recreational drug and excessive alcohol use among HIV-infected men who have sex with men in Central Israel - Zohar Mor; Dan Turner; Yuval Livnat; Itzchak Levy (BMC, 2019)
Abstract Background HIV-infected men who have sex with men (MSM) who use recreational drugs (RD) or excessive alcohol (EA) may be involved in risky sexual behaviours, including unprotected anal intercourse (UAI). This study describes the prevalence RD/EA-use among HIV-infected MSM, and compares those who used RD/EA with those who did not. Methods This cross-sectional study included HIV-infected MSM who were recruited in a convenient sample from two AIDS-treatment centres and events for HIV-infected MSM in Israel in 2016. Participants completed anonymous questionnaires including RD/EA-use and their sexual behaviours. RD/EA-use was defined as consumption of any psychoactive stimulants or dissociative anaesthetics, or an uptake of alcohol until drunkenness before or during sex. Results Of all 276 HIV-infected MSM, 202 (73.2%) used RD/EA. Those who used RD/EA were younger, reported earlier sexual debut, had more sexual partners, were more likely to perform UAI with casual partners, more commonly involved in paid sex, used psychiatric medications and more likely to be unsatisfied with their health-status compared to those who did not use RD/EA. HIV-infected MSM who used RD/EA reported a lower CD4-count and higher viral-load than those who did not. In a multivariate analysis, being younger, reported earlier sexual debut and been prescribed psychiatric drugs were associated with RD/EA-use among HIV-infected MSM. Conclusions A large proportion of HIV-infected MSM used RD/EA and also engaged in risky sexual behaviours. A subset of HIV-infected MSM can benefit from mental support during their routine treatment at the AIDS treatment centres and should also receive harm reduction intervention by their providers in order to minimize potential risks pertaining to RD/EA-use.